Notch Signaling in B Cell Immune Responses - Garis, Matthew; Garrett-Sinha, Lee Ann (Frontiers in Immunology, 2021)
The Notch signaling pathway is highly evolutionarily conserved, dictating cell fate decisions and influencing the survival and growth of progenitor cells that give rise to the cells of the immune system. The roles of Notch signaling in hematopoietic stem cell maintenance and in specification of T lineage cells have been well-described. Notch signaling also plays important roles in B cells. In particular, it is required for specification of marginal zone type B cells, but Notch signaling is also important in other stages of B cell development and activation. This review will focus on established and new roles of Notch signaling during B lymphocyte lineage commitment and describe the function of Notch within mature B cells involved in immune responses.